Reaksi Organisasi Islam Tentang Pendidikan Islam Tahun 1905-1942 Terhadap Kebijakan Politik Pemerintah Hindia-Belanda - Adikara, Muhammad Agam; Warjio, Warjio; Fauzan, Indra (Universitas Medan Area, 2024)
The Dutch East Indies government's education policy was at the core of colonial politics. The Dutch used education to maintain colonialism in the Dutch East Indies, with the policy of teacher ordinances and illegal schools aimed at limiting indigenous education. This policy was opposed by Indigenous intellectuals, including Islamic intellectuals because it was detrimental to the natives and triggered the reaction of Islamic organizations to oppose it. This research uses descriptive qualitative methods with data triangulation techniques. Thomas R. Dye's public policy theory defined the rational basis for political decision-making. The results showed that the Dutch education policy was not to educate the natives but to provide opportunities for the native elite who supported colonial rule. Dutch concerns about the progress of education in the Dutch East Indies were the cause of this policy, with the potential impact of educational organizations uniting against the Dutch. Researchers recommend equality in education in Indonesia, in contrast to the Kiai-led Islamic education system. The teacher and wild school ordinance policies restricted the development of nationalism and Islam, which were considered to hinder the Dutch mission. The Dutch East Indies government's education policy was at the core of colonial politics. The Dutch used education to maintain colonialism in the Dutch East Indies, with the policy of teacher ordinances and illegal schools aimed at limiting indigenous education. This policy was opposed by Indigenous intellectuals, including Islamic intellectuals because it was detrimental to the natives and triggered the reaction of Islamic organizations to oppose it. This research uses descriptive qualitative methods with data triangulation techniques. Thomas R. Dye's public policy theory defined the rational basis for political decision-making. The results showed that the Dutch education policy was not to educate the natives but to provide opportunities for the native elite who supported colonial rule. Dutch concerns about the progress of education in the Dutch East Indies were the cause of this policy, with the potential impact of educational organizations uniting against the Dutch. Researchers recommend equality in education in Indonesia, in contrast to the Kiai-led Islamic education system. The teacher and wild school ordinance policies restricted the development of nationalism and Islam, which were considered to hinder the Dutch mission.